ANCHORING IN THE POLITICAL AND ECONOMIC MARKETING - Tatyana L. Shklyar (Статистика и экономика, 2016)
The main purpose of marketing, both ineconomy and in politics is to attract themaximum number of customers or voters, maximizing customer satisfaction and ,ideally, improve the quality of life.The author, in various aspects, thetechnology of anchoring used in NLP, to attract customers and voters, both in the economy and in politics.In different examples demonstrate theoverall impact on the psychology of the consumer. Separating policy and the economy, marketers are missing something. The author proposes to look at how psychologicalanchors affect these two, at ﬁ rst glance, different vector.